Phonology - Carr, Philip, 1953-; Montreuil, Jean-Pierre. (New York : Palgrave macmillan, 2013)
"The second edition of this successful introductory guide has been thoroughly updated and expanded to take into account latest developments and current teaching. It features three new chapters on phonological weight (Chapter 10) and Optimality Theory (Chapters 11 and 12), as well as new exercises and suggestions for further readings"--
Machine generated contents note: -- Preface -- Acknowledgements -- Revision of Phonetics -- The Phonemic Principle -- Alternations -- Features, Classes and Systems -- Problems with the Phonemic Principle -- The Organisation of the Grammar -- Abstractness, Psychological Reality and the Phonetics/Phonology Relation -- The Role of the Lexicon -- Representations Reconsidered (i) Phonological Structure above the Level of the Segment -- Representations Reconsidered (ii) Autosegmental Phonology -- Phonological Weight -- Optimality Theory -- Issues in Optimality -- Feature Specifications for Consonants -- Sample Answers to Exercises -- References -- Subject Index -- Language Index.
Includes bibliographical references (pages 322-333) and index.
Keywords: Grammar, Comparative and general -- Phonology; LANGUAGE ARTS & DISCIPLINES / Linguistics / Phonetics & Phonology; LANGUAGE ARTS & DISCIPLINES / Grammar & Punctuation; LANGUAGE ARTS & DISCIPLINES / Linguistics / General